Cybermycelium: a reference architecture for domain-driven distributed big data systems - Ataei, Pouya (Frontiers in Big Data, 2024)
The ubiquity of digital devices, the infrastructure of today, and the ever increasing proliferation of digital products have dawned a new era, the era of big data (BD). This era began when the volume, variety, and velocity of data overwhelmed traditional systems that used to analyse and store that data. This precipitated a new class of software systems, namely BD systems. Whereas BD systems provide a competitive advantage to businesses, many have failed to harness the power of them. It has been estimated that only 20% of companies have successfully implemented a BD project. This is due to various challenges of adopting BD, such as organisational culture, rapid technology change, system development, data architecture, and data engineering. This paper aims to facilitate BD system development, architecture, and data engineering by introducing a domain-driven decentralised BD reference architecture (RA). This artefact was developed following the guidelines of empirically grounded RAs and has been evaluated in a real world scenario. At the end, a prototype of the artefact has been instantiated and utilised to solve a real problem in practice. Our results display a good degree of applicability and some thought-provoking architectural tradeoffs and challenges.